RADIATION SITUATION ON THE TERRITORY OF THE OREL REGION AFFECTED BY THE RADIOACTIVE CONTAMINATION DUE TO THE CHERNOBYL ACCIDENT - G. L. Zakharchenko; E. V. Polyakova; S. N. Milovanov; Yu. M. Efimof (Радиационная гигиена, 2015)
The paper presents the results of radiation situation monitoring on the territory of the Orel region after the accident at the Chernobyl NPP. Actions of the sanitary epidemiological authority for the emergency response management, actions of the region administration for the population protection from the overexposure are analyzed. Data on morbidity of the liquidators of Chernobyl accident and region inhabitants, living on the contaminated territories, is presented.